Eco resistance in the poetry of the Arab poet Mahmoud Darwish - Hamoud Yahya; Zalina Mohd Lazim; Ravichandran Vengadasamy (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
Ecocriticism is a new and growing field and quite a recent phenomenon in the world of literature. This study attempts to analyze three poems of the Arab poet Mahmoud Darwish using selected concepts from eco-criticism as a way of opening up this field to Arab world academics. The premise of this research was impelled by the generally agreed view that every society and culture has their own way of interacting with nature; which in turn can illuminate a culture’s worldviews, norms and values. It can also provide insights as to how nature has been used by certain poets to further their agendas. The study mainly dwells on selected poems that have natural objects as their main focus and which show how Darwish utilized nature as a form of resistance to colonialism. Such poems of Darwish could be used to illustrate how eco-criticism might contribute to an understanding of Arab resistance during the colonialist period. The research shows that the Arab poet, Mahmoud Darwish had a special way of educating Arab people to resist through “green” poems that were engineered on natural environment.